Pengaruh Pemberian Konsentrasi Gula Lontar pada Dendeng Ikan Tembang (Sardinella fimbriata) terhadap Lama Simpan berdasarkan Kadar Air, Nilai Organoleptik dan Total Cemaran Mikroba - Satria K. Frans; Annytha Ina Rohi Detha; Elisabet Tangkonda (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Dendeng is a traditional food results by the public Rote Ndao. Method for making dendeng by drying using sunlight as well as using palm sugar as the main ingredient pickling as well as the addition of spices. This study aims to determine the effect of the use of palm sugar in the manufacture of Dendeng Ikan. The processing is done in the District Lobalain(Rote Ndao). Methods of use of the sugar palm consisting of 4 treatments, KO (without giving sugar palm), K1 (10% concentration of palm sugar), K2 (20% concentration of palm sugar), K3 (30% concentration of palm sugar), K4 (40% concentration palm sugar). 4 times the storage of dendeng with the observation that the 5th day (P1), 10th day (P2), 15th day (P3), 20th day (P4). The quality of dendeng observed included presentations lost water content after processing, testing organoleptic and microbiological quality in terms of Total Plate Count (TPC). The test results of water content during storage of dendeng showed that, giving palm sugar concentration of 40% in the processing of fish dendeng, has a water content lower than the palm sugar concentration of 10%, 20% and 30%. During storage, less than the 15th day dendeng with palm sugar concentration giving 40% meet the Standar Nasional Indonesia moisture content, while the dendeng with the provision of palm sugar concentration of 30% has less storage than day-to-5 that meets the water content of the Standar Nasional Indonesia. The test results showed that the organoleptic, Giving palm sugar concentration levels in the processing of fish dendeng affect the appearance, consistency / texture, aroma and taste of dendeng. During storage in certain storage time of each treatment dendeng change the appearance, consistency / texture, aroma and taste. The test results TPC (Total Plate Count) of dendeng showed that, giving the concentration of sugar palm sugar palm 40% in the processing of dendeng, has a value of TPC (Total Plate Count) is lower than the concentration of sugar palm 10%, 20%, and 30 %. During storage, only on day 5 dendeng with palm sugar concentration giving 40% to abide by the TPC (Total Plate Count) of Standar Nasional Indonesia.